The use of genomics for improving livestock production - Mapholi-Tshipuliso, Ntanganedzeni Olivia (University of the Free State, 2008)
The goal of the study was to examine ways in which molecular genetics can be used to enhance the performance and sustainability of beef cattle production. A review of the literature of livestock and poultry was included to describe different approaches previously used for quantitative trait loci (QTL) studies, followed by two case studies. The first case study was to detect QTLs that affect relative amounts of saturated (SFA), monounsaturated (MUFA) and polyunsaturated (PUFA) fatty acids using 328 F2 progeny of Wagyu x Limousin F1 derived from eight Wagyu founder bulls. The search was implemented with 217 markers covering the 29 bovine autosomes. A total of six QTLs were found which are located on five different chromosomes; on a genome-wide basis two were statistical significant and four were suggestive QTLs. On BT A2, a QTL was found that had additive effects on SFA (4 cM, F = 10.07, P = 0.04), MUFA (4 cM, F = 23.62, P < 0.01) and PUFA (11 cM, F = 20.74, P < 0.01). Two QTLs with dominance effects on MUFA were observed on BTA9 (P = 0.04; 2 QTL vs. I QTL). Three additional suggestive QTLs for dominant effects on the relative amounts of fatty acids were also detected. A QTL affecting the PUF A content were observed at 31 cM on BTAIO (F = 9.22; P = 0.06) and at 12 cM on BTA15 (F = 9.67, P = 0.06). Finally, a QTL affecting the MUFA content was found at 47 cM on BTA22 (F = 9.62, P= 0.08). A second case study included an experimental data that was analyzed and divided into two components: I) to validate the pedigree expectation of genomic contributions to successive generations of backcrossing at loci unlinked to the locus being introgressed; and 2) to examine the effectiveness of the introgression strategy. Experimentally, backcrossing a self coat colour pattern into Line I Hereford was attempted. The two founder populations, Fl cross, two subsequent generations of backcrossing, and an intercross generation were evaluated. In total 526 were genotyped using 34 unlinked and five linked microsatellite markers. Estimated contributions of Line I Hereford in the Fi, B1 and B2 generations were 0.500, 0.750, and 0.875, compared to expected contributions based on a pedigree of 0.540, 0.746, and 0.819. In this study, the introgression was compromised because the linked markers used did not sufficiently segregate between the founder populations however more markers will be required for further research. Finally, to integrate the knowledge gained in the preceding studies, an experiment was designed to identify QTLs that have effect on tick resistance, carcass weight and carcass quality in Nguni and Angus cattle using the F2 design. If successful, the results of this study might lead to use of marker assisted introgression to increase resistance to tick of South African Angus and (or) add value to the carcass quality and carcass weight to Nguni.
Dissertation (M.Sc. (Genetics))--University of the Free State, 2008
Keywords: Quantitative trait loci; Genetic markers; Beef quality; Fatty acids; Backcrossing; Nguni; Beef cattle -- Breeding; Dairy cattle -- Breeding; Dairy cattle -- Genetic engineering; Beef cattle -- Genetic engineering